Influence of operating conditions on the efficiency of the wet cleaning of flue gases from ash particles - Fedinchyk I.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2013)
Improvement of the efficiency of the wet cleaning of flue gases of coal-fired boiler from ash particles is an important environmental problem. Apparatus for the wet cleaning of flue gases (scrubbers) are widely spread in Ukrainian power engineering but their efficiency often doesn’t meet the present-day requirements, although the possibilities of improvement of their work are far from being exhausted. The most reasonable way of solution of this problem is connected with mathematic modeling. Such a model has been built with the author’s participation, the program GLS5 was developed this basis. With its help, we have performed numerical investigations of the state evolution of a three-phase medium as applied to the process of gas cleaning in a hollow scrubber.On the example of basic variant of calculations, we have analyzed the laws of change in the velocity, temperature and specific flow rate of drops and particles along the flow length. We have studied the dependence of the efficiency of ash catching on water consumption and the initial velocities of drops and gas. It has shown that particle catching becomes better with increase in the scrubber watering and drop velocity and also with decrease in the gas velocity. We have also explained the dependences obtained.